(untitled) (KULT_online, 2010)
İhsan Bayraktarlı’s doctoral thesis Die politische Debatte um die türkische Schrift- und Sprachrevolution von 1928 (The political debate on the reform of the Turkish language and writing system of 1928) focuses on the analysis of political and linguistic aspects of Turkish writing system reform. The main topics are the study of the adoption of the Latin alphabet (1928) and the analysis of linguistic purism (1932). A detailed discussion of language planning processes in Turkey forms the core of the thesis. A contrastive comparison is carried out using similar developments in the Soviet Union and Western Europe, followed by a look at current linguistic and educational policies in Turkey.